BS LADY: COMMUNITY MARKETING SEBAGAI STRATEGI KOMUNIKASI PEMASARAN DARI BUTTONSCARVES - Farras Muthiah (UNIVERSITAS STEKOM, 2025)
BS Lady, the designation for the brand community of the luxury hijab brand Buttonscarves, is renowned for their loyalty towards the brand. These enthusiasts are willing to queue for hours and pay prices far above the market value to acquire their coveted products. Additionally, the BS Lady community often organically organizes gatherings that strengthen their bond. This article aims to understand Buttonscarves' community marketing strategy by identifying the activations undertaken by Buttonscarves in developing the BS Lady community. The methods employed include informant interviews and observation of marketing communication activities carried out by Buttonscarves. After analyzing Buttonscarves' community marketing activations using the consumer journey, this article found that Buttonscarves has perfected the consumer shopping experience. For pre-purchase-stage consumers, Buttonscarves activates initiatives that enhance awareness by collaborating with public figures and renowned companies. Meanwhile, for purchase-stage consumers, Buttonscarves releases limited-edition series and employs gamification strategies through BS Lady Points to curb impulsive behavior. Finally, for post-purchase consumers, Buttonscarves strengthens their relationship with BS Lady by releasing a special series named BIMU and organizing various community events. This ongoing community marketing strategy is supported by Buttonscarves consistently selecting and shaping values that align with the target market of Buttonscarves.